Implementation of "Treat‐all" at adult HIV care and treatment sites in the Global IeDEA Consortium: results from the Site Assessment Survey. Issue 7 (12th July 2019) - Brazier, Ellen; Maruri, Fernanda; Duda, Stephany N; Tymejczyk, Olga; Wester, C William; Somi, Geoffrey; Ross, Jeremy; Freeman, Aimee; Cornell, Morna; Poda, Armel; Musick, Beverly S; Zhang, Fujie; et al.
Abstract: Introduction: Since 2015, the World Health Organization (WHO) has recommended that all people living with HIV (PLHIV) initiate antiretroviral treatment (ART), irrespective of CD4+ count or clinical stage. National adoption of universal treatment has accelerated since WHO's 2015 "Treat All" recommendation; however, little is known about the translation of this guidance into practice. This study aimed to assess the status of Treat All implementation across regions, countries, and levels of the health care delivery system. Methods: Between June and December 2017, 201/221 (91%) adult HIV treatment sites that participate in the global IeDEA research consortium completed a survey on capacity and practices related to HIV care. Located in 41 countries across seven geographic regions, sites provided information on the status and timing of site‐level introduction of Treat All, as well as site‐level practices related to ART initiation. Results: Almost all sites (93%) reported that they had begun implementing Treat All, and there were no statistically significant differences in site‐level Treat All introduction by health facility type, urban/rural location, sector (public/private) or country income level. The median time between national policy adoption and site‐level introduction was one month. In countries where Treat All was not yet adopted in national guidelines, 69% of sites reported initiating all patients on ART, regardless of clinical criteria, and these sites had been implementing Treat All for a median period of seven months at the time of the survey. The majority of sites (77%) reported typically initiating patients on ART within 14 days of confirming diagnosis, with 60% to 62% of sites implementing Treat All in East, Southern and West Africa reporting same‐day ART initiation for most patients. Conclusions: By mid‐ to late‐2017, the Treat All strategy was the standard of care at almost all IeDEA sites, including rural, primary‐level health facilities in low‐resource settings. While further assessments of site‐level capacity to provide high‐quality HIV care under Treat All and to support sustained viral suppression after ART initiation are needed, the widespread introduction of Treat All at the service delivery level is a critical step towards global targets for ending the HIV epidemic as a public health threat.